2013
DOI: 10.1128/aac.00555-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Drug Resistance in Clinical Candida Species Isolated from Tunisian Hospitals

Abstract: c Antifungal resistance of Candida species is a clinical problem in the management of diseases caused by these pathogens. In this study we identified from a collection of 423 clinical samples taken from Tunisian hospitals two clinical Candida species (Candida albicans JEY355 and Candida tropicalis JEY162) with decreased susceptibility to azoles and polyenes. For JEY355, the fluconazole (FLC) MIC was 8 g/ml. Azole resistance in C. albicans JEY355 was mainly caused by overexpression of a multidrug efflux pump of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 56 publications
1
84
1
4
Order By: Relevance
“…However, antifungals have been used extensively for the prophylaxis or treatment of candidiasis, and there are increasing reports of azole resistance for this species (13,14,27,54). In fact, the azole-resistant clinical isolates of C. tropicalis studied in this work were recovered from two patients suffering from candidemia and treated with different antifungals (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, antifungals have been used extensively for the prophylaxis or treatment of candidiasis, and there are increasing reports of azole resistance for this species (13,14,27,54). In fact, the azole-resistant clinical isolates of C. tropicalis studied in this work were recovered from two patients suffering from candidemia and treated with different antifungals (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Other ERGgene defects also confer multi-drug-resistance [98]. Alterations in sterol-and phospholipid composition as well as changes in membrane structure account for different polyene-cross-resistance patterns [130,131] and were found in clinical isolates resistant to Azoles as well as polyenes [98,[132][133][134][135][136][137]. The situation is probably aggravated by the finding that a mutator phenotype caused by a mismatch repair defect is prevalent in C. glabrata [138].…”
Section: Cross Resistance Multidrug Resistance and Horizontal Gene mentioning
confidence: 92%
“…Amino acid alteration in the target enzyme ERG11 or the replacement of Ergosterol by other sterols in the membrane encoded by ERG3 are examples. As Ergosterol being essential for the mode of action of Azoles as well as polyenes is absent in ERG3 loss-of-function mutants, these strains escape the antifungal effect of both drug classes [91][92][93][94][95][96][97][98]. Other ERGgene defects also confer multi-drug-resistance [98].…”
Section: Cross Resistance Multidrug Resistance and Horizontal Gene mentioning
confidence: 99%
“…Deletion of MRR1 in clinical strains blocked MDR1 up-regulation (Morschhauser et al 2007). Fifteen different MRR1 GOF mutations have been reported (Sanglard 2011;Eddouzi et al 2013), causing constitutive up-regulation of MDR1 (Dunkel et al 2008). Genome-wide transcriptional studies using clinical strains revealed a core set of 14 genes involved in diverse functions that are up-regulated in isolates carrying MRR1 GOF mutations (Morschhauser et al 2007).…”
Section: Trans-acting Elementsmentioning
confidence: 99%